2008
DOI: 10.1002/mrm.21771
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative bone matrix density measurement by water‐ and fat‐suppressed proton projection MRI (WASPI) with polymer calibration phantoms

Abstract: The density of the organic matrix of bone substance is a critical parameter necessary to clinically evaluate and distinguish structural and metabolic pathological conditions such as osteomalacia in adults and rickets in growing children. Water-and fat-suppressed proton projection MRI (WASPI) was developed as a noninvasive means to obtain this information. In this study, a density calibration phantom was developed to convert WASPI intensity to true bone matrix density. The phantom contained a specifically desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 22 publications
(25 reference statements)
1
59
0
2
Order By: Relevance
“…For example, Techawiboonwong et al have compared the signal from bone and a water phantom to quantify bone water concentration as a new metric of bone quality in human cortical bone in vivo [6,12]. Cao et al have also compared the signal from bone with a polymer calibration phantom, and found that the MR signal could be used to obtain true bone matrix mass density [23].…”
Section: Discussionmentioning
confidence: 98%
“…For example, Techawiboonwong et al have compared the signal from bone and a water phantom to quantify bone water concentration as a new metric of bone quality in human cortical bone in vivo [6,12]. Cao et al have also compared the signal from bone with a polymer calibration phantom, and found that the MR signal could be used to obtain true bone matrix mass density [23].…”
Section: Discussionmentioning
confidence: 98%
“…Notably, there is currently no technique other than magnetic resonance to quantify changes of the bone’s hydration state in situ . Recent work indicates that the majority of the proton signal observed in cortical bone is due to exchangeable water (as opposed to organic matrix) (1, 30) even though matrix constituents can also contribute to the solid-state MRI signal (9). …”
Section: Discussionmentioning
confidence: 99%
“…Our group has been engaged in developing 31 P solid-state magnetic resonance imaging (SMRI) to visualize bone mineral [21–23], and quantitative water- and fat-suppressed proton projection MRI (WASPI) to visualize solid bone matrix [2426]. With these new methods, MRI measurements of bone mineral and matrix density have become available.…”
Section: Introductionmentioning
confidence: 99%